2019
DOI: 10.1051/0004-6361/201935044
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the properties of HD 206893 B

Abstract: Context. High contrast imaging enables the determination of orbital parameters for substellar companions (planets, brown dwarfs) from the observed relative astrometry and the estimation of model and age-dependent masses from their observed magnitudes or spectra. Combining astrometric positions with radial velocity gives direct constraints on the orbit and on the dynamical masses of companions. A brown dwarf was discovered with the VLT/SPHERE instrument at the Very Large Telescope (VLT) in 2017, which orbits at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
64
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 19 publications
14
64
1
Order By: Relevance
“…We determine an eccentricity of e=0.25 +0.17 −0.14 with a 2σ credible interval of 0.0-0.44. Our constraints are narrower than the general unrestricted fit from Delorme et al and are similar to the recent results from Grandjean et al (2019), who also included relative astromety, RVs, and absolute astrometry of the host star from Hipparcos and Gaia in their orbit fit.…”
Section: Uniform Orbits With Literature Astrometrysupporting
confidence: 82%
See 1 more Smart Citation
“…We determine an eccentricity of e=0.25 +0.17 −0.14 with a 2σ credible interval of 0.0-0.44. Our constraints are narrower than the general unrestricted fit from Delorme et al and are similar to the recent results from Grandjean et al (2019), who also included relative astromety, RVs, and absolute astrometry of the host star from Hipparcos and Gaia in their orbit fit.…”
Section: Uniform Orbits With Literature Astrometrysupporting
confidence: 82%
“…When considering only orbits coplanar with the debris disk, this collapses to a range of about e=0.0-0.4. More recently, Grandjean et al (2019) combine relative astrometry, a radial acceleration, and astrometric acceleration measured between Hipparcos and Gaia to constrain the orbit and dynamical mass of HD 206893 B. They find a low eccentricity (e 0.4) and potential evidence of a second companion based on the larger-than-expected radial acceleration.…”
Section: Uniform Orbits With Literature Astrometrymentioning
confidence: 99%
“…HD206893 is a F5V star that hosts a directly imaged BD companion at a separation of 270 mas (Milli et al 2017;Delorme et al 2017). We recently reported in Grandjean et al (2019) a long-term trend in the star RV coupled with pulsations with periods slightly less than one day. We performed an MCMC on both the RV trend, imaging data, and HIPPARCOS-Gaia proper motion measurements to constrain the orbit and dynamical mass of the BD.…”
Section: Hd206893mentioning
confidence: 96%
“…The orbital properties of HD206893B were revisited by Grandjean et al (2019), who performed a joint fit to radial velocity (RV) monitoring, Hipparcos and Gaia astrometry, and SPHERE and NaCo imaging to infer an orbital period for the companion of 21-33 yr. They derived its dynamical mass to be a potentially planetary mass of -+ M 10 4 5 Jup .…”
mentioning
confidence: 99%
“…They derived its dynamical mass to be a potentially planetary mass of -+ M 10 4 5 Jup . However, Grandjean et al (2019) noted that the fit appears dominated by the Hipparcos-Gaia proper-motion constraints, as the estimated mass from the joint fit is inconsistent at the 2σ level with the mass derived from the combination of only direct imaging astrometry and RV variation. The authors thus posit that the "B" companion cannot be responsible for the observed 1.6yr RV drift, and that this variation may correspond instead to an additional ∼15 M Jup interior companion with a short 1.6-4yr period.…”
mentioning
confidence: 99%